Design of a low profile omnidirectional antenna for V2X communications - Chen, Xiaoli (2015)
This project aims to make innovative designs and simulations of a low profile antenna with omnidirectional radiation to replace a commercial product with high profile used for a large NTU V2X research program by using the state-of-the-art simulation software called HFSS. A new circular disk microstrip antenna had been designed for the V2X communications and analyzed. Such antenna has low profile and omnidirectional radiation pattern. The antenna consists of a circular radiating disk and one ring or two ring radiating patches that locate at the center of top side of a circular substrate, a ground plane on the bottom side of the circular substrate and a feed point locate at the center of the substrate. The cavity model [4] is used to analyze the circular disk microstrip antenna, which can give a good physical insight of each TMnm mode in order to serve as a good guideline of designing the circular disk microstrip antenna. This designed antenna will work at TM02 mode and has an omnidirectional radiation pattern. The designed antenna had been sent to fabrication. The fabricated antenna has an omnidirectional radiation pattern, a low profile of 1.6 mm thickness and a working bandwidth of 5.47 to 6.07 GHz. The measured return loss and radiation pattern of the fabricated antenna almost agrees with the simulation results. In addition, an improved circular disk microstrip antenna is also simulated and analyzed. It is twice the height of the substrate as compared with previous fabricated antennas. Generally speaking, the improved circular disk microstrip antenna has a much wider bandwidth, better impedance match and higher gain.